2019
DOI: 10.1186/s41936-018-0070-2
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of taurine and/or vanillin against renal, testicular, and hematological alterations induced by potassium bromate toxicity in rats

Abstract: Background: Potassium bromate (KBrO 3 ) causes toxicity in humans and experimental animals. The wide exposure to KBrO 3 in water disinfection and as a food additive necessitates finding of available antidotes for its hazards as taurine and/or vanillin. Aim: The present study was conducted to investigate the protective effects of taurine and/or vanillin against potassium bromate toxicity on renal, testicular, and hematological parameters in adult male albino rats. Methods: For this purpose, 30 rats were divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…The findings of this investigation showed that KBrO 3 caused an inflammatory response that was manifested by an increase in renal TNFand IL-6 levels, indicating nephrotoxicity. This is comparable to the increase in TNF-and IL-6 levels found in rats exposed to potassium bromate, as reported by Mohamed and Saddek [32]. Recently, Ugwu et al [58] found that KBrO 3 caused oxidative stress in the rat kidney.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The findings of this investigation showed that KBrO 3 caused an inflammatory response that was manifested by an increase in renal TNFand IL-6 levels, indicating nephrotoxicity. This is comparable to the increase in TNF-and IL-6 levels found in rats exposed to potassium bromate, as reported by Mohamed and Saddek [32]. Recently, Ugwu et al [58] found that KBrO 3 caused oxidative stress in the rat kidney.…”
Section: Discussionsupporting
confidence: 84%
“…Degradation of purines and pyrimidines may potentially be a contributing factor to the rise in uric acid levels. According to a study by Mohamed and Saddek [32], KBrO 3 increased xanthine oxidase activity, which resulted in an excess of uric acid being produced. This process may have led to the action of KBrO 3 in the increase of uric acid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with a previous study conducted by Bashandy et al 54 Sialic acid is an N-acetylmannose derivative that is an important component of glycolipids and glycoproteins. 55 The obtained results showed that there was a significant decrease in testicular sialic acid level in untreated FeSO 4 -incubated testicular tissues (Figure 7). This decrease in testicular sialic acid levels could be attributed to a slowing of spermatogenesis.…”
Section: Discussionmentioning
confidence: 82%
“…9 Administration of KBrO 3 significantly elevated IL-6, this is consistent with other previous studies. [62][63][64] MET, AuNPs, and METAuNPs groups decreased IL-6. These findings correlate with the report of Al-Hashem et al 50 which showed that metformin suppresses thioacetamide inflammatory response.…”
Section: Discussionmentioning
confidence: 99%